The Effect of Air Ionizers Installation on Motorcycle Performance - Afdhal Zikri; Martias Martias; Toto Sugiarto (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2019)
An air ionizer device can produce negative ion which ionizes the air, can be used for engine air induction system for improving the quality of fuel mixture that increase the engine output of power & torque. Test is done by using a dynamometer by comparing power & torque with installed air ionizer active and inactive. Data analysis technique using descriptive analysis of formula ttest with 5% of significant level. The t test results showed a significant increase in maximum power under active air ionizer conditions (tcount 5,128> ttable 4,303) with a significant level of 5%, increase 0.8 HP or 11.7% of inactive air ionizer with a value 7.2 HP to 8.0 HP. Meanwhile, the maximum torque shows an insignificant increase (tcount = 0.929 <ttable = 4,303) with a significant level of 5%, increase 0.5 Nm or 6.9% of inactive air ionizer with a value of 7.24 Nm to 7, 74 Nm.